A diáspora coreana: o caso brasileiro - Bruna Mineo Antonio; José Renato de Campos Araújo (Confins)
This paper seeks to present and general characteristics of the Korean diaspora within its historical context, highlighting the Korean immigration in Brazil, especially in the city of. Thus, from the literature on the history of Korea, administrative records and official documents, the objective of this work is to present the Korean migratory flow to Brazil, with the city of São Paulo being its main destination, from its origin to the present moment. With such a presentation we can observe the importance of this migrant group within the social and economic dynamics of the urban fabric of São Paulo, as well as demonstrate how the interethnic relationship between migrant groups with important elements of interculturality marks the history of the city of São Paulo. The descriptive mark of the text is based on the low academic production on the Korean diaspora fixed in Brazil, even though international migrations are a deep trace in the history and development of the metropolis of São Paulo.